Registered nurses' psychological capital: A scoping review - Flinkman Mervi; Coco Kirsi; Rudman Ann; Leino-Kilpi Helena (WILEY, 2025)
Aims: The aim was to examine the extent and scope of empirical research concerning registered nurses' psychological capital.
Background: In a time of global nursing shortage, identifying variables that could positively contribute to the retention of the nursing workforce is essential. Prior research has shown that psychological capital correlates positively with employees' better performance and well-being.
Design: A scoping review.
Data sources: A systematic literature search was conducted in the following databases: PubMed, CINAHL, PsycINFO, Web of Science and Scopus covering the period from 1 January 2005 to 7 May 2023.
Review methods: The JBI methodological guidance for scoping reviews was followed. The results were summarized narratively.
Results: A total of 111 studies reported in 114 peer-reviewed articles were included. Studies were carried out across 20 countries, with the majority from China (45), Australia (nine), Pakistan (nine), Canada (eight), South Korea (eight) and the United States (eight). A positive correlation was found between registered nurses' psychological capital and desirable work-related outcomes, such as work engagement, commitment and retention intention.
Conclusion: A comprehensive overview of research evidence suggests that psychological capital is associated with many positive work-related outcomes and might therefore be a valuable resource for reducing nurse turnover.